استخدام طلاب قسم المکتبات والمعلومات بجامعة بنها الفیسبوک Facebook کمصدر من مصادر المعلومات الالکترونیة التى تدعم المقررات الدراسیة - د. سها بشیر أحمد (المجلة الدولية لعلوم المكتبات والمعلومات)
The present study aims to identifying to what extent the students ofthe Department of Libraries and Information at Banha University usedFacebook as a source of electronic information that supports courses, Andreasons for use and non-use, based on the field approach. Thequestionnaire was used as a data collection tool. The study sample ofFacebook users in the educational process reached (234) students. Amongthe most important results of the study, encouraging the vast majority ofstudents (81.6%) to use Facebook in education. They also stressed thatFacebook is a source of electronic information that supports courses, W hilenon-users pointed out to Facebook that the main reason for non-use is notto have a computer connected to the Internet, (76%) of non-users ofFacebook stressed that they have a real desire to use Facebook in thefuture and that the main means Which they rely on to obtain the informationthat supports the courses were represented in the library search andinquire from friends